Genetic engineering and genome editing technologies as catalyst for Africa’s food security: the case of plant biotechnology in Nigeria - Adegbaju, Muyiwa Seyi; Ajose, Titilayo; Adegbaju, Ifeoluwa Elizabeth; Omosebi, Temitayo; Ajenifujah-Solebo, Shakirat Oloruntoyin; Falana, Olaitan Yetunde; Shittu, Olufunke Bolatito; Adetunji, Charles Oluwaseun; Akinbo, Olalekan (Frontiers in Genome Editing, 2024)
Many African countries are unable to meet the food demands of their growing population and the situation is worsened by climate change and disease outbreaks. This issue of food insecurity may lead to crisis of epic proportion if effective measures are not in place to make more food available. Thus, deploying biotechnology towards improvement of existing crop varieties for tolerance or resistance to both biotic and abiotic stresses is crucial towards increasing crop production. In order to optimize crop production, several African countries have implemented strategies to make the most of this innovative technology. For example, Nigerian government has implemented the National Biotechnology Policy (NBP) to facilitate capacity building, research, bioresources development and commercialization of biotechnology products for over two decades. Several government ministries, research centers, universities, and agencies have worked together to implement the policy, resulting in the release of some genetically modified crops to farmers for cultivation and commercialization which is a significant accomplishment. However, the transgenic crops were only brought to Nigeria for confined field trials; the manufacturing of the transgenic crops took place outside the country. This may have contributed to the suspicion of pressure groups and embolden proponents of biotechnology as an alien technology. Likewise, this may also be the underlying issue preventing the adoption of biotechnology products in other Africa countries. It is therefore necessary that African universities develop capacity in various aspects of biotechnology, to continuously train indigenous scientists, who can generate innovative ideas tailored towards solving problems that are peculiar to respective country. Therefore, this study intends to established the role of genetic engineering and genome editing towards the achievement of food security in Africa while using Nigeria as a case study. In our opinion, biotechnology approaches will not only complement conventional breeding methods in the pursuit of crop improvements, but it remains the viable and sustainable means of tackling specific issues hindering optimal crop production. Furthermore, we suggest that financial institutions should offer low-interest loans to new businesses in order to promote the growth of biotechnology products, especially through the creation of jobs and revenues through molecular farming.